Aerospace technologies for assessing soil contamination - Golovan, Yu. (ХНУРЕ, 2023)
Studies of soil pollution assessment are based on scientific principles that define a complex system of environmental safety management in the context of increased exposure to sources of secondary dust pollution of the atmosphere. To ensure environmental safety under conditions of high levels of dust pollution, it is necessary to apply and improve the relevant models. Among the many types of environmental pollution, dust pollution of the atmospheric air and the deposition of harmful substances on the soil are particularly dangerous. This pollution can take two forms: direct emissions from industrial enterprises (primary) or the formation of secondary pollution through physical and chemical processes in places where dust-like waste is stored. Fine waste after air purification with dimensions of less than 100 microns is particularly hazardous. In modern environmental monitoring and assessment of soil pollution, special attention is paid to remote methods that allow for more effective monitoring of the impact of human activity and solving environmental problems. The use of unmanned aerial vehicles is one such method that has positive results. The purpose of the article is to solve the scientific problem of improving aerospace methods based on unmanned aerial vehicles (UAVs) for monitoring and assessing the quality of soil pollution. The object of the study is the use of aerospace tools for monitoring and assessing the condition of soil cover. To achieve this goal, the following tasks have been defined: to study the current state and ways to improve the efficiency of UAVs in the system of environmental monitoring of soils; to develop models of environmental assessment; to analyze existing approaches to the use of aerospace assets for monitoring and assessing the state of soil cover. Conclusions: a methodological approach based on a modified method of the comprehensive assessment of the level of technogenic hazard of industrial facilities is proposed to assess the state of environmental safety in conditions of intense dust pollution of the atmospheric air.
Keywords: information technology; technogenic hazard; soil cover; dust pollution; atmospheric air; technical solutions; environmental safety; morbidity